Preoperative skin asepsis protocols using chlorhexidine versus povidone‐iodine in veterinary surgery: A systematic review and meta‐analysis. Issue 5 (18th April 2022) - Marchionatti, Emma; Constant, Caroline; Steiner, Adrian
Abstract: Objective: To provide a systematic assessment of the efficacy of preoperative skin asepsis using chlorhexidine versus povidone‐iodine based protocols for surgical site infection (SSI) prevention in veterinary surgery. Study design: Systematic meta‐analytical review according to PRISMA‐P guidelines. Sample population: Studies comparing preoperative skin asepsis protocols using chlorhexidine versus povidone‐iodine in veterinary surgery identified by systematic search between 1990 and 2020. Methods: A search using MEDLINE/Pubmed, Web of Science and CAB Abstracts was performed, followed by secondary searches of Google Scholar, Proquest Dissertation and Theses, and relevant bibliographic articles. Primary and secondary outcome measures were the efficacy of skin asepsis protocols using chlorhexidine versus povidone‐iodine on SSI incidence and skin bacterial colonization, respectively. A meta‐analysis was performed with a random‐effect model, with effect size calculated as risk ratio (RR) or mean standard deviation (MSD) with 95% CI. Statistical significance was set at P < .05. Results: Among 1067 publications that met the initial search criteria, 9 relevant studies were eligible for analysis. No difference in the incidence of postoperative SSI or skin bacterial colonization between preoperative asepsis protocols using chlorhexidine versus povidone‐iodine was found. Insufficient information and detail were frequent among studies and precluded a clear assessment of bias. Conclusion: This study showed that asepsis protocols using chlorhexidine were comparable to povidone‐iodine in preventing postoperative SSI and reducing skin bacterial colonization. Clinical significance: Given the limitations of the studies that were included in terms of both quality and quantity, more high‐quality randomized controlled trials are needed to confirm these conclusions.